(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The location management of the Mobile Agent and its current updated Location and maintenance in the mobile database and its reliability design are the current issues in a distributed technology. It still represents an open research area. . This paper analyses the new locating management schemes with the graph theory concept and probability reliability design which will make some difference in heterogeneous networks. In this work, a deployment of four type of locators protocols are proposed for optimal and fault tolerant free location management technique through mobile agent such as HSL, OSL, ICL ,UZL and sub locators as IZHSL, IZOSL, IZICL. The theoretical model of graph theory optimization technique is used for optimal throughput of updated LA (location area) which is residing under the structure of BA and MSC. To achieve the reliability design the theoretical method of Tie-setCut-set approach is proposed. A simulation is performed and the result of location updates through deployment of locators is achieved.